The resistivity structure of the Penola Trough, Otway Basin from magnetotelluric data. Issue 5 (3rd July 2016) - Kirkby, A.; Heinson, G.; Holford, S.
ABSTRACT: We present inversion results for a 100 site, broadband magnetotelluric (MT) survey in the Penola Trough, Otway Basin, South Australia. The Penola Trough is host to several petroleum reservoirs and has more recently been a target for unconventional geothermal exploration. We present two interpretations of the MT data. A 1D anisotropic interpretation, where anisotropy is determined within the Otway Basin sequence and basement in the northeastern Penola Trough, fits the impedance tensor well. However, the anisotropy strike is inconsistent with the known orientation of electrically conductive fractures in the Penola Trough. On the other hand, a 3D interpretation, which incorporates lateral variations in resistivity, requires no anisotropy yet it matches the data equally well. Both the 1D and 3D inversions resolve several layers within the Otway Basin sequence, which correspond to stratigraphic units defined in wells and in the coincident Haselgrove–Balnaves 3D seismic survey. These include the Eumeralla and Dilwyn formations, which are poorly resolved in the seismic data. The basin architecture, defined in the 3D inversion, in particular the depth to basement, is consistent with previous interpretations based on seismic reflection data that show that the Otway Basin thins in the northeastern Penola Trough. This does not occur in the anisotropic model. We therefore conclude that the subsurface resistivity appears to be isotropic in the Penola Trough. This contrasts with the anisotropic resistivity structure determined in a previous study in the Koroit region, eastern Otway Basin. The difference in the MT responses between the two regions is supported by resistivity and permeability information from well logs and may reflect differences in the orientation of subsurface fractures, or differences in the present-day stress field, between the two regions.